موقع أرنتروبوس: -التجربة،الواقع والآفاق- - بوطقوقة, مبروك (Changement Social, 2018)
Writing the word " anthropology" in googlesearchengineisenough to get a complete and a clearpicture of the poorArabic digital content of anthropology as a science. A novice personwho look want to make a research on thisfieldwillbeamazed by millions of English and French websitesproviding a bigamount of information. On the other hand, weeasilyfind out the pooramount of information regarding the Arabic content. This shocking reality isundeniable to anyresearcher of the field. Throughthispaper, I willmake a comprehensiveresearchwith a special focus on the first and greateranthropological site: aranthropos.com, wichbecames a must for researchers and students in this discipline.